How useful are the cold pressor test and sustained isometric handgrip exercise with radionuclide ventriculography in the evaluation of patients with coronary artery disease?. Issue 4 (April 1987) - Northcote, R J; Cooke, M B
Abstract : The feasibility of using the cold pressor test and the sustained isometric handgrip test as alternatives to dynamic exercise for stressing the heart was investigated. Serial changes in heart rate, blood pressure, and left ventricular performance induced by these tests were studied by radionuclide ventriculography in patients with coronary artery disease and in normal volunteers. Both tests significantly increased heart rate and blood pressure. The reproducibility of serial evaluation of ejection fraction response to cold pressor and isometric handgrip stresses was satisfactory but the sensitivity for detecting coronary artery disease was not. Both stress tests are valuable interventions for the serial evaluation of left ventricular function by radionuclide ventriculography, but they should not be used to detect coronary artery disease.